Food-induced brain activity in adult obesity: a quantitative electroencephalographic study (Faculty of Medicine Universitas Indonesia, 2023)
BACKGROUND Obesity may be associated with declined food consumption control through neurological and behavioral processes, as well as heightened responsiveness of the brain’s reward systems. Performing neuroimaging and neurophysiological methods such as electroencephalography (EEG) can examine the connection between brain function and behavior. This study aimed to identify brain regulation of feeding behavior to food cues, which could be a potential neuromodulatory intervention target in adult obesity. METHODS This cross-sectional study was conducted at Cipto Mangunkusumo Hospital, Jakarta, involving 40 adults with obesity. EEG analysis was performed to measure electrophysiological brain activity during eyes-open condition and during exposure to high-calorie food cues. Student’s t-tests were performed to identify any significant differences between the groups (p<0.05). RESULTS Beta waves in the frontal (channel F7) and gamma waves in the central (channels C3 and C4) and parietal (channels P3 and P4) regions were significantly increased during food cues compared to resting state/eyes-open condition without stimulation. Theta waves in the frontal (channels F7 and F8), central (channel C3), and parietal (channels P3 and P4) regions and alpha waves in the central (channels C3 and C4) and parietal (channels P3 and P4) regions were significantly decreased during food cues compared with resting state. CONCLUSIONS In adults with obesity, increased beta activity in the frontal and gamma in the central and parietal regions suggested increased food-cue awareness and heightened attentional focus toward food stimuli. Additionally, decreased alpha and theta activities in frontal regions could underline deficits in executive functions and higher motivation.